Disease progression in blepharospasm: a 5‐year longitudinal study. (12th November 2018) - Ferrazzano, G.; Conte, A.; Gigante, A.; Defazio, G.; Berardelli, A.; Fabbrini, G.
Abstract : Background and purpose: The clinical manifestation of dystonic spasms in blepharospasm (BSP) patients may be heterogeneous. Whether the varying phenomenology of eyelid spasms becomes manifest sequentially during the course of the disease or aggregates in separate clusters according to different disease courses is still unclear. For this purpose, the clinical features in BSP patients were evaluated longitudinally over a 5‐year period and also the blink reflex recovery cycle was tested in a subgroup of BSP patients. Methods: Sixty BSP patients were videotaped at time 0 and after approximately 5 years of follow‐up. Two experts in movement disorders, who were blinded to the video order, reviewed the videotapes and scored the severity of BSP using the Blepharospasm Severity Rating Scale. Changes in the R2 recovery index were also evaluated in 18 patients twice, i.e. upon enrolment and at the follow‐up. Results: The severity of BSP worsened significantly over the 5‐year follow‐up period owing to the appearance or the increased duration and frequency of prolonged spasms. It was also found that the blink reflex recovery cycle worsened at follow‐up in comparison with the baseline. Conclusions: This study shows that the disease progression of BSP is characterized by the appearance or worsening of prolonged spasms. Prolonged spasms are accompanied by changes in the excitability of brainstem interneurons. Aging‐related effects may exacerbate the pathophysiological mechanisms underlying spasms.